C programming tutoring simulation with interactive multimedia "cyberc" / Goh Lee Ching - Goh , Lee Ching (2004)
Technology gives us physical access to a wealth of information. However, the information housed on servers throughout the globe and in software and print resources is so abundant that finding what one needs is a daunting task. Information literacy has the duty to put that information to good use. CyberC is a web-based interactive multimedia learning package system developed for anyone whom is interested in learning knowledge on C programming. CyberC is designed to create an information rich environment of education resources.which can be obtained at any time and from any place to ave the users time. Lessons and quizzes will be laid out to offer user interactive multimedia learning experience. Besides these, there will be games and more fun elements to allow users to have an enjoyable time. Rapid Application Development Model i used to develop CyberC. This model emphasizes on prototyping loops which will means iterative process to ensure best quality product. The development tools include Macromedia Dreamweaver MX Macromedia Flash MX, JavaScript, ActionScript, ASP.NET and Microsoft Access 2002. It is hoped that CyberC will be able to promote users interest toward C programming, which is powerful and useful. Various approaches are implemented in CyberC to ensure maximum knowledge Inferred and available. After all learning starts when you enjoy it.